2014
DOI: 10.1007/s11682-014-9289-9
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation during neurocognitive testing using functional near-infrared spectroscopy in patients following concussion compared to healthy controls

Abstract: There is no accepted clinical imaging modality for concussion, and current imaging modalities including fMRI, DTI, and PET are expensive and inaccessible to most clinics/ patients. Functional near-infrared spectroscopy (fNIRS) is a non-invasive, portable, and low-cost imaging modality that can measure brain activity. The purpose of this study was to compare brain activity as measured by fNIRS in concussed and age-matched controls during the performance of cognitive tasks from a computerized neurocognitive test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 51 publications
4
53
2
Order By: Relevance
“…Second, a cross‐sectional design does not allow for application of this project's recovery trends for oxyhaemoglobin concentration and its variances, to a single patient in a clinical setting. And third, the present study, in addition to the other NIRS‐concussion literature (Kontos et al ., ; Urban et al ., ), all have such unique methodologies and procedures, that it hinders the ability to draw a broader conclusion about the use of NIRS with concussion. Said differently, a hallmark of science is independent reproduction of an experiment, where one must be able to come to a similar outcome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, a cross‐sectional design does not allow for application of this project's recovery trends for oxyhaemoglobin concentration and its variances, to a single patient in a clinical setting. And third, the present study, in addition to the other NIRS‐concussion literature (Kontos et al ., ; Urban et al ., ), all have such unique methodologies and procedures, that it hinders the ability to draw a broader conclusion about the use of NIRS with concussion. Said differently, a hallmark of science is independent reproduction of an experiment, where one must be able to come to a similar outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the first haemoglobin‐concussion publication utilized functional NIRS (fNIRS) to measure relative haemoglobin changes in the frontal lobe and assessed the coupling of cortical activity to metabolite delivery during the ImPACT test. In general, the results showed that concussed participants, (who were still exhibiting symptoms 15–45 days post‐injury), had less changes in oxyhaemoglobin (HbO 2 ) during the ImPACT test and performed worse on the test outcomes when compared to controls (Kontos et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…It is desired to determine changes in hemoglobin (Hb) concentration of brain tissues. According to this method, brain functions related to non-invasive oxygenation, changes in blood oxygenation and blood density are displayed by viewing the blood flow in the forebrain [3]. Metabolic responses arising as a result of each task, such as oxy-and deoxyhemoglobin changes during a point-offocus, allow the using of fNIRS or hybridization of electroencephalogram (EEG) and fNIRS in BCI systems.…”
Section: Introductionmentioning
confidence: 99%